2020
DOI: 10.1038/s42003-020-01288-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analyses reveal modulation of adaptive and innate immune subsets by tuberculosis vaccines

Abstract: We characterize the breadth, function and phenotype of innate and adaptive cellular responses in a prevention of Mycobacterium tuberculosis infection trial. Responses are measured by whole blood intracellular cytokine staining at baseline and 70 days after vaccination with H4:IC31 (subunit vaccine containing Ag85B and TB10.4), Bacille Calmette-Guerin (BCG, a live attenuated vaccine) or placebo (n = ~30 per group). H4:IC31 vaccination induces Ag85B and TB10.4-specific CD4 T cells, and an unexpected NKTlike subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Alternative T cell-mediated resistance IFNγ independent or unconventional T cell responses might play role in the early clearance mechanism. BCG re-vaccination in humans was recently shown to boost the populations of Th1-type CD4 + T cells, expressing IFNγ, IL-2, and/or TNF, as well as CD4 + T cells expressing IL-22, highlighting the importance of unbiased analyses of vaccination responses to discover previously neglected populations 77. Th17 cells, a subset of CD4 + T cells, have been shown to confer protection against Mtb infection in murine adoptive transfer models.…”
mentioning
confidence: 99%
“…Alternative T cell-mediated resistance IFNγ independent or unconventional T cell responses might play role in the early clearance mechanism. BCG re-vaccination in humans was recently shown to boost the populations of Th1-type CD4 + T cells, expressing IFNγ, IL-2, and/or TNF, as well as CD4 + T cells expressing IL-22, highlighting the importance of unbiased analyses of vaccination responses to discover previously neglected populations 77. Th17 cells, a subset of CD4 + T cells, have been shown to confer protection against Mtb infection in murine adoptive transfer models.…”
mentioning
confidence: 99%
“…164 Also, BCG revaccination boosts IL-22 + CD4 + T cells in addition to Th1 cells. 186 Another trial conducted in South Africa in TST + 18-40-year-olds revealed that BCG revaccination significantly boosts pre-existing BCG-specific cytokine + (IFNγ/ IL-2/TNFα/IL-22/IL-17) CD4 + and CD8 + responses at 5 weeks postadministration. Apart from adaptive T cell responses, revaccination also boosted BCG-reactive IFNγ + NKT, NK, and γδ T cells.…”
Section: Bcg Revaccinationmentioning
confidence: 99%
“…Similarly, induction of NKT-like cells in humans vaccinated with the subunit vaccine candidate H4:IC31 was associated with TCR-independent, cytokine-mediated activation. 171 In the absence of IL-12/IL-18, Mtb control by murine iNKT-cells depended on CD1d and granulocyte-macrophage-colony-stimulating factor (GM-CSF). GM-CSF is associated with control of intracellular mycobacterial proliferation in vitro and with protective immunity in mice, 172,173 and was shown to be induced by Mtb antigens in in vitro human studies.…”
Section: (Invariant) Nkt-cells In Immunity Against Mtbmentioning
confidence: 99%
“…Nevertheless, the complex interactions occurring in vivo need to be addressed carefully. For instance, in addition to classical immune responses, BCG vaccination could induce trained immunity on NK cells, ILC-production of IFN-γ, and an array of DURT-mediated immune responses 62,101,171,208,214,215. The delivery route of the vaccine is an important factor to consider, since intravenous BCG vaccination of NHP induced the transient recruitment of MAIT-cells and Vγ9 + TCRγδ T-cells to the lung, and was associated with protection to Mtb challenge 62.…”
mentioning
confidence: 99%